Productions of Edward Albee's plays in Slovenia and the critics' response - Polonca Zalokar (Acta Neophilologica, 2009)
The article focuses on Edward Albee's four plays belonging to the theatre of the absurd which have been performed in Slovene theatres so far. The author analyses Albee's The 'Zoo Story, which has been produced four times, his American Dream and A Delicate Balance, which have been performed only once, and Albee's most known work in Slovenia, Who's Afraid of Virginia Woolf?, which has been produced six times in Slovene theatres. The continuation of this article focuses on  each of Albees above mentioned four plays including their production details, directors, actors, the comparison of critics' opinions and an estimation of how SIovene audiences accepted them according to the number of spectators and critics' responses.